Unravelling the Genetic Basis of Dentinogenesis Imperfecta - Dr Maleeha Gilani; Associate Professor Robert Anthonappa (Elsevier, 2023)
Aim or Purpose: Dentinogenesis imperfecta (DI) is an autosomal dominant genetic disorder affecting dentine formation. This study aimed to perform mutational analysis in individuals with DI to unravel its molecular mechanisms. Materials and Methods: The University of Western Australia Human Research Ethics Committee (RA/4/20/4203) approved this genetic association study. Following a clinical and radiographic examination, 15 individuals participated in this study. All participants' genomic DNA was obtained from peripheral blood lymphocytes for whole-exome sequencing (WES) and Sanger sequencing to detect gene variants, followed by bioinformatics analysis. Results: This study is the first to conduct WES in an Australian population and provide evidence of novel mutations associated with DI. Nevertheless, further research should investigate the functional impact of these mutations. Conclusions: The findings of this study will help us to understand the molecular pathogenesis of DI as well as the normal process of dentine biomineralisation.